Application of Intraoperative Radiotherapy in Early-Stage Breast Cancer Patients in a Clinical Setting - Ao Wang; Elchanan Quint; Ivan Kukeev; Ravit Agassi; Olga Belochitski; Gay Barski; Julie Vaynshtein (International Journal of Breast Cancer)
Conclusion: Our findings suggest that IORT in selected low-risk patients can achieve an excellent prognosis with low rates of recurrence and metastasis.